Human papillomavirus (HPV) as the causal factor of tympanal cholesteatoma in malignant-type chronic suppurative otitis media - Bambang Udji Djoko Rianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Tympanal cholesteatoma is an uncoordinated, uncontrolled hyperproliferative epidermic epithelial cells keratinized with aggressive, erosive and destructive development to the mucous membrane and the bone of external auditory canal and tympanic cavity. This process is invasive and may migrate to the surrounding tissue. Ethiopathogenesis of tympanic cholesteatoma is unknown. Histological examination shows that there are hyperproliferative development, papillomatous, koilocyte clusters and destruction of the bone. These abnormalities are characteristics of papillomavirus.Objective: To know the whether HPV-18 is the risk factor in the occurrence of tympanic cholesteatoma ini malignant-type chronic suupurative otitis media.Methods: A case-control study was conducted on 31 tympanal cholesteatoma specimens from malignanttype chronic suppurative otitis media as the case group, and 31 mucosal tympanic cavity specimens from benign-type chronic suppurative otitis media as the control group. For detecting Polymerase chain reaction (PCR) examination was used to detect DNA HPV-18, that performed in Parasitology laboratorium Faculty of Medicine, Gadjah Mada University.Results: Polymerase chain reaction (PCR) examination showed that there were 21 (67.7%) DNA HPV-18 positive specimens in the case group, while in the control group there were 5 (16.1 %) DNA HPV-18 positive specimens. This difference was statistically significant (p = 0.0001; Odds ratio: 1 0.92; 95 % confidence interval = 2.83-45.29). Immunohistochemistry examination was used to identify host immune response to HPV, by observing the interleukin-1 IIl-1) and interferon g IIFN g) expressions. Both Il-1 and IFN g cytokines were highly expressed in tympanic cholesteatoma samples, compared to both in the control group. The difference was statistically significant (p < 0.05, Odds ratio 14.29; 95% confidence interval: 3.64-60.5 and p< 0.05, Odds ratio:10.2; 95% confidence interval: 2.74-40.35, respectively). Conclusion: It can be concluded that HPV-18 DNA was iidentified, and was one of the multiple risk factors in the occurence of tympanic cholesteatoma in malignant-type chronic suppurative otitis media..Key words: tympanal cholesteatoma - human papillomavirus - malignant-type chronic suppurative otitis media